ABOUT INFORMATION POTENTIAL OF REPORTING, BASED ON RUSSIAN AND INTERNATIONAL PRINCIPLES - A. Bodyako (Вестник университета)
The the information potential of reporting as a collection of information that has already been recorded on information media and on the basis of which users form their own view of the economic sustainability of the reporting economic entity, which are formed on a generally accepted conceptual basis at the international level is disclosed. The article considers the options for the valuation of assets and liabilities that are allowed by international financial reporting standards (IFRS), information support of management decisions. Conclusions are drawn that the structure of corporate reporting has changed significantly, has become branched in composition and information is heterogeneous in content, offers suggestions for its filling in digitalization, digitalization, the use of which will increase the level of information support for management decisions.